New records of mosquito species (Diptera: Culicidae) from Neuquén and La Rioja provinces, Argentina - Grech, Marta Gladys (2012)
The presence of Aedes aegypti is reported beyond its current limit of distribution in Argentina, in the city of Neuquén, Neuquén Province. Ovitraps were placed to collect Ae. aegypti eggs between December 2009 and April 2010. The geographical distribution of Culex eduardoi, Psorophora ciliata and Ps. cingulata is extended with new records from two provinces.